Alkaline Earth Metal Aluminates as Catalysts for Imine Hydrogenation - Elsen, Holger; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Organometallics, 2020)
Alkaline earth (Ae) metal complexes with the alanate anion AlH4 - have been prepared by salt metathesis between NaAlH4 and AeCl2 in THF and could be isolated as Mg(AlH4)2·(THF)4, Ca(AlH4)2·(THF)4, and Sr(AlH4)2·(THF)5. The previously reported crystal structure of the Mg alanate complex shows bonding of AlH4 - with one bridging hydride, H3Al-(μ-H)-Mg, while the Ca and Sr alanates show a combination of H3Al-(μ-H)-Ae and H2Al-(μ-H)2-Ae bridging. The heteroleptic β-diketiminate complexes (DIPPBDI)Mg(AlH4)·THF and (DIPPBDI)Ca(AlH4)·(THF)2 have been prepared by reaction of the corresponding Ae hydride complexes with AlH3·(THF)2 [DIPPBDI = DIPP-NC(Me)C(H)C(Me)N-DIPP, where DIPP = 2,6-diisopropylphenyl]. Crystal structures show H2Al-(μ-H)2-Ae bridging. The Ca complex decomposes at room temperature by reduction of the β-diketiminate anion. Density functional theory calculations (B3PW91/def2tzvpp) show that the formation of Ae(AlH4)2 from AeH2 and AlH3 is exothermic by ΔH (kilocalories per mole): Be, -68.8; Mg, -66.1; Ca, -95.4; Sr, -100.9; Ba, -112.3. Calculations of NPA charges on LiAlH4 and the Ae alanate complexes (Ae = Mg, Ca, or Sr) show that these are highly ionic salts in which the charge on AlH4 - of approximately -0.95 is hardly dependent on the countercation. Compared to LiAlH4, the Ae alanates are very efficient catalysts for imine hydrogenation, clearly extending the substrate scope. In addition to aldimines RC(H)═NR′ (R/R′ = Ph/tBu, tBu/tBu, nPr/tBu, or Ph/Ph), ketimine PhC(Me)═NtBu could be reduced. The salt [Bu4N+][AlH4 -] is catalytically not active, which shows that the s-block metal is crucial. The highest activities were found for the heterobimetallic Ca and Sr alanates.
CRIS-Team Scopus Importer:2020-06-09

Alkaline Earth Metal Imido Complexes with Doubly Deprotonated Amidine and β-Diketimine Ligands - Martin, Johannes; Langer, Jens; Elsen, Holger; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
Double deprotonation of the amidine DIPP-N=C(tBu)-NH2 or β-diketimine DIPP-N=C(Me)-C(H)=C(Me)-NH2 (DIPP = 2,6-diisopropylphenyl) with strong benzylcalcium or strontium bases gave metal imido complexes with the anions DIPP-N=C(tBu)-N2– (Am2–) and DIPP-N=C(Me)-C(H)=C(Me)-N2– (BDI2–) which crystallized as tetrameric complexes with typical Ca4N4 or Sr4N4 cubane frameworks. Crystal structures of [(Am)Ca·THF]4, [(BDI)Ca·THF]4 and the first Sr imido complex [(Am)Sr·THF]4 are presented. Calculated geometries of [(Am)Ca·THF]4 and [(BDI)Ca·THF]4 (B3PW91/6-311++G**) are in good agreement with the crystal structures. Also complexes with monoanionic ligands (Am-H)– and (BDI-H)– are reported. Charge delocalization in the ligand backbone is discussed. Ligand–metal bonds are calculated to be circa 90 % ionic; the NPA charges on Ca is circa +1.8. The negative charge on the ligand is delocalized over the ligand backbone but there is still considerable electron density on the terminal N (–1.4). Despite this high negative charge, the reactivity of these complexes is generally low due to the strongly bound cubane core. Reaction of [(Am)Ca·THF]4 with phenyl cyanide gave the [(Am)Ca·PhCN]4, clearly demonstrating its low reactivity. Attempts to break the tetrameric cluster in smaller aggregates by addition of 18-crown-6 led to protonation and isolation of (Am-H)2Ca·(18-crown-6). Reaction of [(Am)Ca·THF]4 with iPrN=C=NiPr gave after addition a complex with a unique amido-guanidinate ligand.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Alkaline earth metals; Amidinates; Density functional calculations; Imido ligands; β-Diketiminates

Bulky cationic β-diketiminate magnesium complexes - Friedrich, Alexander; Pahl, Jürgen; Elsen, Holger; Harder, Sjoerd (Dalton Transactions, 2019)
Cationic β-diketiminate Mg complexes with the bulky tBu BDI ligand and the weakly coordinating anion B(C 6 F 5 ) 4 - have been prepared by the reaction of ( tBu BDI)MgnBu with [Ph 3 C] + [B(C 6 F 5 ) 4 ] - ; tBu BDI = CH[C(tBu)N-Dipp] 2 and Dipp = 2,6-diisopropylphenyl. Their structures are compared to the previously reported cationic ( Me BDI)Mg + complexes; Me BDI = CH[C(Me)N-Dipp] 2 . Crystallization of [( tBu BDI)Mg] + [B(C 6 F 5 ) 4 ] - from chlorobenzene gave a unique ( tBu BDI)Mg + ·ClC 6 H 5 cation with a rather short Mg⋯Cl and consequently long C-Cl bond. Crystallization from chlorobenzene/arene solvent mixtures gave ( tBu BDI)Mg + ·arene complexes (arene = benzene, toluene, m-xylene) but in the presence of mesitylene the chlorobenzene complex was formed. Due to the greater shielding of the metal, none of these complexes display Mg⋯(F 5 C 6 ) 4 B - interactions. Crystal structures of the arene complexes show in all cases η 2 -coordination of the arene ligands. Ring slippage from a more favorable η 2 -coordination can be explained by the steric bulk of the tBu BDI ligand. The smaller arenes, benzene and toluene, also bind to ( tBu BDI)Mg + in bromobenzene solution. The Lewis acidity of these cationic Mg complexes was determined by the Gutmann-Beckett test. The acceptor number for ( tBu BDI)Mg + (AN = 76.0) is substantially higher than that estimated for ( Me BDI)Mg + (AN = 70.3). Calculation of the atomic NPA charges by DFT shows that the Mg 2+ ion in ( tBu BDI)Mg + is slightly more positively charged than the metal in ( Me BDI)Mg + , confirming its higher Lewis acidity. The lower benzene complexation energy calculated for ( tBu BDI)Mg + versus ( Me BDI)Mg + is due to steric congestion of the metal in the ( tBu BDI)Mg + cation which allows only for Mg⋯(η 1 )C 6 H 6 instead of Mg⋯(η 6 )C 6 H 6 bonding. This ring slippage, however, results in a significant polarization of the electron density in the benzene ring, making it susceptible for nucleophilic attack..
CRIS-Team Scopus Importer:2019-05-09

Calcium-Catalyzed Arene C-H Bond Activation by Low-Valent Al-I - Brand, Steffen; Elsen, Holger; Langer, Jens; Grams, Samuel; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
The low-valent ss-diketiminate complex ((BDI)-B-DIPP)Al is stable in benzene but addition of catalytic quantities of [((BDI)-B-DIPP)CaH](2) at 20 degrees C led to ((BDI)-B-DIPP)Al(Ph)H ((BDI)-B-DIPP=CH[C(CH3)N-DIPP](2), DIPP=2,6-diisopropylphenyl). Similar Ca-catalyzed C-H bond activation is demonstrated for toluene or p-xylene. For toluene a remarkable selectivity for meta-functionalization has been observed. Reaction of ((BDI)-B-DIPP)Al(m-tolyl)H with I-2 gave m-tolyl iodide, H-2 and ((BDI)-B-DIPP)AlI2 which was recycled to ((BDI)-B-DIPP)Al. Attempts to catalyze this reaction with Mg or Zn hydride catalysts failed. Instead, the highly stable complexes ((BDI)-B-DIPP)Al(H)M((BDI)-B-DIPP) (M=Mg, Zn) were formed. DFT calculations on the Ca hydride catalyzed arene alumination suggest that a similar but more loosely bound complex is formed: ((BDI)-B-DIPP)Al(H)Ca((BDI)-B-DIPP). This is in equilibrium with the hydride bridged complex ((BDI)-B-DIPP)Al(mu-H)Ca((BDI)-B-DIPP) which shows strongly increased electron density at Al. The combination of Ca-arene bonding and a highly nucleophilic Al center are key to facile C-H bond activation.
CRIS-Team WoS Importer:2019-10-01

Cationic Aluminium Complexes as Catalysts for Imine Hydrogenation - Friedrich, Alexander; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Pahl, Jürgen; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2021)
Strongly Lewis acidic cationic aluminium complexes, stabilized by β–diketiminate (BDI) ligands and free of Lewis bases, have been prepared as their B(C6F5)4− salts and were investigated for catalytic activity in imine hydrogenation. The backbone (R1) and N (R2) substituents on the R1,R2BDI ligand (R1,R2BDI=HC[C(R1)N(R2)]2) influence sterics and Lewis acidity. Ligand bulk increases along the row Me,DIPPBDI<Me,DIPePBDI≈tBu,DIPPBDI<tBu,DIPePBDI; DIPP=2,6-C(H)Me2-phenyl, DIPeP=2,6-C(H)Et2-phenyl. The Gutmann-Beckett test showed acceptor numbers of: (tBu,DIPPBDI)AlMe+ 85.6, (tBu,DIPePBDI)AlMe+ 85.9, (Me,DIPPBDI)AlMe+ 89.7, (Me,DIPePBDI)AlMe+ 90.8, (Me,DIPPBDI)AlH+ 95.3. Steric and electronic factors need to be balanced for catalytic activity in imine hydrogenation. Open, highly Lewis acidic, cations strongly coordinate imine rendering it inactive as a Frustrated Lewis Pair (FLP). The bulkiest cations do not coordinate imine but its combination is also not an active catalyst. The cation (tBu,DIPPBDI)AlMe+ shows the best catalytic activity for various imines and is also an active catalyst for the Tishchenko reaction of benzaldehyde to benzylbenzoate. DFT calculations on the mechanism of imine hydrogenation catalysed by cationic Al complexes reveal two interconnected catalytic cycles operating in concert. Hydrogen is activated either by FLP reactivity of an Al⋅⋅⋅imine couple or, after formation of significant quantities of amine, by reaction with an Al⋅⋅⋅amine couple. The latter autocatalytic Al⋅⋅⋅amine cycle is energetically favoured.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Aluminium; cations; DFT; hydrogenation; imine

Dibenzotropylidene Substituted Ligands for Early Main Group Metal-Alkene Bonding - Martin, Johannes; Langer, Jens; Wiesinger, Michael; Elsen, Holger; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
New N-ligands with TROP-substituents are introduced (TROP = [5H]dibenzo[a,d]cyclohepten-5-yl): (TROP)(DIPP)N (DIPP = 2,6-diisopropylphenyl), TROPBDI (HC[C(Me)N-TROP]2) and the β-diketiminate ligand TROP–DIPPBDI with TROP and DIPP substituents at N. Several Li, Mg, Ca and Zn complexes with these ligands have been isolated and were characterized by X-ray diffraction. While TROP-substituents in the protonated ligands show endo-exo exchange, TROP-substituents in the metal complexes are in endo-conformation due to metal···alkene bonding. Short contacts between the metal and the TROP alkene unit are observed and some of these are the shortest reported; (TROPBDI)Li: Li···C 2.416(3) Å, [(TROP)(DIPP)N]2Ca: Ca···C 2.742(2) Å. TROPBDI shows superior metal shielding properties to the Li complex with a buried volume of VB = 78.7 %. DFT calculations on [(TROP)(DIPP)N]2Mg show a minimum with asymmetric Mg···alkene bonding. Symmetric Mg···alkene bonding is a transition state 1.9 kcal/mol higher in energy. Asymmetry in alkene-Mg bonding is explained by an ion-induced polarization of the C=C bond and electrostatic Mg2+···(δ-)C=C(δ+) attraction. The TROP-substituent stabilizes low valent radical species but attempts to isolate (TROPBDI)Mg· or (TROPBDI)Zn· by reduction of the iodide precursors failed. Intensely black coloured raw products hint towards formation of radical species. Several radical decomposition products have been structurally characterized.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Amides; Early main group metals; Metal-alkene bonding; Radicals; β-Diketiminate

Dipyrromethene and beta-Diketinninate Zinc Hydride Complexes: Resemblances and Differences - Ballmann, Gerd; Grams, Samuel; Elsen, Holger; Harder, Sjoerd (Organometallics, 2019)
A new dipyrromethene (DPM) ligand with bulky DIPP-substituents is introduced (DIPP = 2,6-diisopropylphenyl). The ligand, abbreviated as (DPM)-D-DIPP, was deprotonated with ZnEt2 to give ((DPM)-D-DIPP)ZnEt, which reacted with I-2 to form ((DPM)-D-DIPP)ZnI. Reaction of the latter with K[N(Pr-i)HBH3] afforded a labile Zn amidoborane complex which, after beta-hydride elimination, formed ((DPM)-D-DIPP)ZnH. Crystal structures of ((DPM)-D-DIPP)ZnX (X = Et, I, H) revealed their monomeric nature. The Zn-N bond distances are somewhat longer than those in the corresponding, monomeric beta-diketiminate complexes ((BDI)-B-DIPP)ZnX ((BDI)-B-DIPP = CH[C(Me)N-DIPP](2)). This is in agreement with calculated NPA charges, which are lower on the N atoms of DPM compared to those on BDI. Reaction of ((DPM)-D-DIPP)ZnH with CO2 gave ((DPM)-D-DIPP)Zn(O2CH), which crystallized as a monomer with a symmetrically bound eta(2)-formate ligand. In contrast, the beta-diketiminate complex crystallizes as a dimer [((BDI)-B-DIPP)Zn(O2CH)](2) with bridging formate ligands. Reaction of ((DPM)-D-DIPP)Zn(O2CH) with various silanes regenerated the hydride complex ((DPM)-D-DIPP)ZnH. Catalytic CO2 hydrosilylation with (EtO)(3)SiH using ((DPM)-D-DIPP)ZnH as a catalyst gave full reduction to [Si]-OMe species, whereas the catalyst ((BDI)-B-DIPP)ZnH only partially reduced CO2 to [Si]-OC(O)H. The advantage of the (DPM)-D-DIPP ligand is the arrangement of the DIPP-substituents, which form a pocket around the Zn-X unit, preventing dimerization and influencing its reactivity. In addition, in contrast to the negatively charged central backbone carbon in the (BDI)-B-DIPP ligand, that in (DPM)-D-DIPP is neutral. This makes it less nucleophilic and Bronsted basic, as expected for a true spectator ligand.
CRIS-Team WoS Importer:2019-08-09

Early Main Group Metal Catalysts for Imine Hydrosilylation - Elsen, Holger; Fischer, Christian; Knüpfer, Christian; Escalona, Ana; Harder, Sjoerd (Chemistry - A European Journal, 2019)
The efficient catalytic reduction of imines with phenylsilane is achieved by using the potassium, calcium and strontium based catalysts [(DMAT)K (THF)]∞, (DMAT)2Ca⋅(THF)2 and (DMAT)2Sr⋅(THF)2 (DMAT=2-dimethylamino-α-trimethylsilylbenzyl). Eight different aldimines and the ketimine Ph2C=NPh could be successfully reduced by PhSiH3 at temperatures between 25–60 °C with catalyst loadings down to 2.5 mol %. Also, simple amides like KN(SiMe3)2 or Ae[N(SiMe3)2]2 (Ae=Ca, Sr, Ba) catalyze this reaction. Activities increase with metal size. For most substrates the activity increases along the row K
CRIS-Team Scopus Importer:2019-11-29
Keywords: alkaline earth metals; density functional calculations; hydrosilylation; imines; potassium

Heterometallic Mg−Ba Hydride Clusters in Hydrogenation Catalysis - Wiesinger, Michael; Knüpfer, Christian; Elsen, Holger; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (ChemCatChem, 2021)
Reaction of a MgN“2/BaN”2 mixture (N“=N(SiMe3)2) with PhSiH3 gave three unique heterometallic Mg/Ba hydride clusters: Mg5Ba4H11N”7 ⋅ (benzene)2 (1), Mg4Ba7H13N“9 ⋅ (toluene)2 (2) and Mg7Ba12H26N”12 (3). Product formation is controlled by the Mg/Ba ratio and temperature. Crystal structures are described. While 3 is fully insoluble, clusters 1 and 2 retain their structures in aromatic solvents. DFT calculations and AIM analyses indicate highly ionic bonding with Mg−H and Ba−H bond paths. Also unusual H−⋅⋅⋅H− bond paths are observed. Catalytic hydrogenation with MgN“2, BaN”2 and the mixture MgN“2/BaN”2 has been studied. Whereas MgN“2 is only active in imine hydrogenation, alkene and alkyne hydrogenation needs the presence of Ba. The catalytic activity of the MgN”2/BaN“2 mixture lies in general between that of its individual components and strong cooperative effects are not evident.
CRIS-Team Scopus Importer:2021-09-17
Keywords: alkaline earth metal; catalysis; DFT calculations; heterometallic; hydride

Insights into LiAlH4 Catalyzed Imine Hydrogenation - Elsen, Holger; Langer, Jens; Ballmann, Gerd; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2020)
Commercial LiAlH4 can be used in catalytic quantities in the hydrogenation of imines to amines with H2. Combined experimental and theoretical investigations give deeper insight in the mechanism and identifies the most likely catalytic cycle. Activity is lost when Li in LiAlH4 is exchanged for Na or K. Exchanging Al for B or Ga also led to dramatically reduced activities. This indicates a heterobimetallic mechanism in which cooperation between Li and Al is crucial. Potential intermediates on the catalytic pathway have been isolated from reactions of MAlH4 (M=Li, Na, K) and different imines. Depending on the imine, double, triple or quadruple imine insertion has been observed. Prolonged reaction of LiAlH4 with PhC(H)=NtBu led to a side-reaction and gave the double insertion product LiAlH2[N]2 ([N]=N(tBu)CH2Ph) which at higher temperature reacts further by ortho-metallation of the Ph ring. A DFT study led to a number of conclusions. The most likely catalyst for hydrogenation of PhC(H)=NtBu with LiAlH4 is LiAlH2[N]2. Insertion of a third imine via a heterobimetallic transition state has a barrier of +23.2 kcal mol−1 (ΔH). The rate-determining step is hydrogenolysis of LiAlH[N]3 with H2 with a barrier of +29.2 kcal mol−1. In agreement with experiment, replacing Li for Na (or K) and Al for B (or Ga) led to higher calculated barriers. Also, the AlH4− anion showed very high barriers. Calculations support the experimentally observed effects of the imine substituents at C and N: the lowest barriers are calculated for imines with aryl-substituents at C and alkyl-substituents at N.
CRIS-Team Scopus Importer:2020-12-04
Keywords: DFT; heterobimetallic; hydride; hydrogenation; imine

Large decanuclear calcium and strontium hydride clusters - Martin, Johannes; Eyselein, Jonathan; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Chemical Communications, 2020)
Two large decanuclear hydride clusters of the general formula Ae10H16[N(R)R']4·(PMDTA)2 (Ae = Ca, Sr) were isolated. Both derivatives feature a [Ae10H16]4+ core, consisting of two edge shared metal octahedra with interstitial hydrides, while the other hydrides cap triangular faces.
CRIS-Team Scopus Importer:2020-08-21

Lewis acidic alkaline earth metal complexes with a perfluorinated diphenylamide ligand - Fischer, Christian; Rösch, Andreas; Elsen, Holger; Ballmann, Gerd; Wiesinger, Michael; Langer, Jens; Färber, Christian; Harder, Sjoerd (Dalton Transactions, 2019)
Alkaline earth metal (Ae) chemistry with the anion [N(C 6 F 5 ) 2 ] - has been explored. Deprotonation of the amine (C 6 F 5 ) 2 NH, abbreviated in here as N F H, with 0.5 equivalent of AeN′′ 2 (N′′ = N(SiMe 3 ) 2 ) is fast and gave, dependent on the solvent, the complexes AeN F 2 , AeN F 2 ·(THF) 2 and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca, Sr). Using a 1/1 ratio, mixed amide complexes were obtained: N F AeN′′ (Ae = Mg, Ca, Sr). Crystal structures of the monomers AeN F 2 ·(THF) 2 (Ae = Mg, Ca, Sr) and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca) are presented and compared with those of AeN′′ 2 ·(THF) 2 . In addition, crystal structures of the homoleptic dimer (MgN F 2 ) 2 and the heteroleptic dimers (N F AeN′′) 2 (Ae = Mg, Ca, Sr) are discussed. All structures are strongly influenced by very short Ae⋯F contacts down to circa 2.11 Å (Mg), 2.50 Å (Ca) and 2.73 Å (Sr). AIM analysis illustrates that, although Ae⋯F contacts are short, there is no bond-critical-point along this axis, indicating an essentially electrostatic interaction. The monomeric complexes feature strong C 6 F 5 ⋯C 6 F 5 π-stacking, resulting in unusually acute N F -Ae-N F angles as small as 95°. Heteroleptic (N F AeN′′) 2 complexes retain their dimeric structure in C 6 D 6 solution and there is no indication of ligand scrambling by the Schlenk equilibrium, suggesting that an electron withdrawing ligand may stabilize heteroleptic complexes. According to DFT calculations, the heteroleptic arrangement is 70 kJ mol -1 more stable than the homoleptic dimers. The Lewis acidity of MgN F 2 has been quantified with the Gutmann-Beckett method and by calculation of the Fluoride-Ion-Affinity. The latter calculations show that the Lewis acidity of MgN F 2 and CaN F 2 is comparable to that of B(C 6 F 5 ) 3 . Dimeric (MgN F 2 ) 2 fully abstracts Et 3 PO from Et 3 PO·B(C 6 F 5 ) 3 and may have potential in Lewis acid catalysis.
CRIS-Team Scopus Importer:2019-06-04

Lewis Acidic Cationic Strontium and Barium Complexes - Thum, Katharina; Martin, Johannes; Elsen, Holger; Eyselein, Jonathan; Stiegler, Lisa; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Lewis acidic (BDI)Ae+ cations of the heavier metals Sr and Ba, which are not stabilized by polar solvents, have been obtained by double deprotonation of (BDI)H2+ with either SrN’’2 or BaN’’2; BDI = HC[C(Me)N(DIPP)]2, DIPP = 2,6-diisopropylphenyl, Ae = alkaline earth, N’’ = N(SiMe3)2. Due to clathrate formation [(BDI)Ae+][B(C6F5)4−] could not be crystallized, but pyrene addition gave crystalline [(BDI)Ae+ ⋅ pyrene][B(C6F5)4−] which was structurally characterized for Ae = Mg, Ca, Sr, Ba. (R2N)Ae+ cations of the heavier metals Sr and Ba were obtained by reaction of Ae(NR2)2 with [Ph3C+][B(C6F5)4−] or [PhNMe2H+][B(C6F5)4−]. Following complexes were structurally characterized: [N’’Ba+ ⋅ (tol)2][B(C6F5)4−], [N*Sr+ ⋅ PhNMe2][B(C6F5)4−], [N*Ba+ ⋅ tol][B(C6F5)4−] and [N*Ba+ ⋅ C6H6][B(C6F5)4−]; tol = toluene and N* = N(SiiPr3)2. DFT calculations show that Sr⋅⋅⋅PhNMe2 coordination is preferred over Sr⋅⋅⋅toluene bonding. The (R2N)Ae+ cations can be used as Brønsted bases (reaction with (BDI)H gave (BDI)Ae+) and may be useful precursors for a variety of Lewis base-free RAe+ cations. DFT calculations, limited to monomeric model systems including B(C6F5)4− (ωB97XD/def2tzvpp//ωB97XD/def2svp), show that there is negligible electron transfer from the pyrene or toluene ligands to the Ae2+ cation. Electrostatic attraction originates from charge-induced polarization of the (Formula presented.) -electron density in the toluene and pyrene ligands.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Ab initio calculations; Arene coordination; Barium; Cations; Strontium

Ligand Effects in Calcium Catalyzed Ketone Hydroboration - Brand, Steffen; Causero, Andrea; Elsen, Holger; Pahl, Jürgen; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
The first “naked” (Lewis base-free) cationic Ca amidinate complex [tBuAmDIPPCa(C6H6)]+[B(C6F5)4]– was prepared in 62 % yield tBuAmDIPP = tBuC(N–DIPP)2; DIPP = 2,6-diisopropylphenyl by reaction of [tBuAmDIPPCaH]2 with [Ph3C]+[B(C6F5)4]– in chlorobenzene. The ether-free complex tBuAmDIPPCaN(SiMe3)2 was obtained by removal of diethyl ether from its ether adduct. Crystal structures show that the amidinate ligand in both complexes is N,Aryl-chelating. In this coordination mode the bulk of the amidinate ligand is comparable to that of a DIPP-substituted β-diketiminate ligand. Isomers with N,N-coordinating amidinate ligands are circa 15 kcal/mol higher in energy and this coordination mode is only present in case additional ether ligands compensate for energy loss or in case of space limitation at the metal, e.g. in homoleptic (tBuAmDIPP)2Ca. A series of four Ca amidinate complexes, tBuAmDIPPCaX, were tested in the catalytic hydroboration of ketones and aldehydes by pinacolborane (HBpin). Catalytic activities increase for X– = I– < B(C6F5)4 – < (Me3Si)2N– ≈ H–. For catalysts with unreactive anions, like I– or B(C6F5)4 –, catalyst performance increases with the Lewis acidity of the metal and a mechanism is proposed in which HBpin and ketone coordinate to the Ca2+ ion which is followed by direct hydroboration. The more active catalysts with X– = (Me3Si)2N– or H– likely operate through a mechanism which involves intermediate metal hydride (or borate) complexes.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Amidinates; Calcium; Cationic complexes; Homogeneous catalysis; Hydroboration

Low Valent Magnesium Chemistry with a Super Bulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Ballmann, Gerd; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
The steric bulk of the well-known DIPP BDI ligand (CH[C(CH 3 )N-DIPP] 2 , DIPP=2,6-diisopropylphenyl) was increased by replacing isopropyl for isopentyl groups. This very bulky DIPeP BDI ligand could not stabilize the radical species ( DIPeP BDI)Mg . : reduction of ( DIPeP BDI)MgI with Na gave ( DIPeP BDI) 2 Mg 2 with a rather long Mg-Mg bond of 3.0513(8) Å. Addition of TMEDA prior to reduction gave complex ( DIPeP BDI) 2 Mg 2 (C 6 H 6 ), which could also be obtained as its THF adduct. It is speculated that combination of a bulky spectator ligand and TMEDA prevents dimerization of the intermediate Mg I radical, which then reacts with the benzene solvent. Complex ( DIPeP BDI) 2 Mg 2 (C 6 H 6 ), which formally contains the anti-aromatic anion C 6 H 6 2− , reacted with tBuOH as a Brønsted base to 1,3- and 1,4-cyclohexadiene and with H 2 as a two electron donor to ( DIPeP BDI) 2 Mg 2 H 2 and C 6 H 6 . It also reductively cleaved the C−F bond in fluorobenzene and gave ( DIPeP BDI)MgPh, ( DIPeP BDI)MgF, and C 6 H 6 .
CRIS-Team Scopus Importer:2019-08-16
Keywords: alkaline earth metal; bulky ligand; low valence; magnesium; metal-metal bonding

Magnesium Cyanide or Isocyanide? - Ballmann, Gerd; Elsen, Holger; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
Preference for the binding mode of the CN- ligand to Mg (Mg-CN vs. Mg-NC) is investigated. A monomeric Mg complex with a terminal CN ligand was prepared using the dipyrromethene ligand (DPM)-D-Mes which successfully blocks dimerization. While reaction of ((DPM)-D-Mes)MgN(SiMe3)(2) with Me3SiCN gave the coordination complex ((DPM)-D-Mes)MgN(SiMe3)(2).NCSiMe3, reaction with ((DPM)-D-Mes)Mg(nBu) led to ((DPM)-D-Mes)MgNC.(THF)(2). A Mg-NC/Mg-CN ratio of approximate to 95:5 was established by crystal-structure determination and DFT calculations. IR studies show absorbances for CN stretching at 2085 cm(-1) (Mg-NC) and 2162 cm(-1) (Mg-CN) as confirmed by C-13 labeling. In solution and in the solid state, the CN ligand rotates within the pocket. The calculated isomerization barrier is only 12.0 kcal mol(-1) and the C-13 NMR signal for CN decoalesces at -85 degrees C (Mg-NC: 175.9 ppm, Mg-CN: 144.3 ppm). Experiment and theory both indicate that Mg complexes with the CN- ligand should not be named cyanides but are more properly defined as isocyanides.
CRIS-Team WoS Importer:2019-10-08

Nucleophilic Aromatic Substitution at Benzene with Powerful Strontium Hydride and Alkyl Complexes - Rösch, Bastian; Gentner, Thomas; Elsen, Holger; Fischer, Christian; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
Key to the isolation of the first alkyl strontium complex was the synthesis of a strontium hydride complex that is stable towards ligand exchange reactions. This goal was achieved by using the super bulky beta-diketiminate ligand (BDI)-B-DIPeP (CH[C(Me)N-DIPeP](2), DIPeP = 2,6-diisopentylphenyl). Reaction of (BDI)-B-DIPeP-H with Sr[N(SiMe3)(2)](2) gave ((BDI)-B-DIPeP)SrN(SiMe3)(3) which was converted with PhSiH3 into [((BDI)-B-DIPeP)SrH2]. Dissolved in C6D6, the strontium hydride complex is stable up to 70 degrees C At 60 degrees C, H-D isotope exchange gave full conversion into ([(BDI)-B-DIPeP)SrD](2) and C6D5H. Since H-D exchange with D-2 is facile, the strontium hydride complex served as a catalyst for the deuteration of C6H6 by D-2. Reaction of [( (BDI)-B-DIPeP)SrH](2) with ethylene gave [( (BDI)-B-DIPeP)SrEt](2). The high reactivity of this alkyl strontium complex is demonstrated by facile ethylene polymerization and nucleophilic aromatic substitution with C6D6, giving alkylated aromatic products and [((BDI)-B-DIPeP)SrD](2).
CRIS-Team WoS Importer:2019-04-23

Retro-Diels-Alder decomposition of norbornadiene mediated by a cationic magnesium complex - Thum, Katharina; Pahl, Jürgen; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2021)
First evidence for the coordination of norbornadiene (nbd) and dicyclopentadiene (dcpd) with the main group metal Mg is provided by the crystal structures of adducts with cationic beta-diketiminate (BDI) Mg complexes. While the dcpd complex is thermally stable, [(BDI)Mg+center dot nbd][B(C6F5)(4)(-)] shows slow room temperature retro-Diels-Alder decomposition to give a complex with the cation (BDI)Mg(C5H5)Mg(BDI)(+).
CRIS-Team WoS Importer:2021-05-28

s-Block Metal Dibenzoazepinate Complexes: Evidence for Mg-Alkene Encapsulation - Freitag, Benjamin; Elsen, Holger; Pahl, Jürgen; Ballmann, Gerd; Herrera, Alberto Cesar; Dorta, Romano; Harder, Sjoerd (Organometallics, 2017)

Silver cation tagged on 5,7,12,14-tetraphenyl-6,13-diazapentacene and its dihydro-form - Kinzelmann, Marina; Oschwald, Johannes; Elsen, Holger; Warmbrunn, Vera; Hauschild, Miriam; Harder, Sjoerd; Kivala, Milan; Drewello, Thomas (Physical Chemistry Chemical Physics, 2023)
The attachment of silver(i) cations to 5,7,12,14-tetraphenyl-6,13-diazapentacene and its reduced dihydro-form has been studied by electrospray ionization mass spectrometry (ESI-MS). The structure elucidation of the Ag+ complexes has been accomplished in gas-phase collision experiments in conjunction with density functional theory (DFT) calculations. The oxidized form provides a favourable cavity for the Ag+ ion, leading to the [1 : 1] complex with the highest resilience towards dissociation and severely hindering the attainment of a second molecular ligand. When the nitrogen is hydrogenated in the reduced dihydro-form, the cavity is partly blocked. This leads to a less strongly bound [1 : 1] complex ion but facilitates the attachment of a second molecular ligand to the Ag+. The resulting complex is the most stable among the [2 : 1] complexes. DFT calculations provide valuable insight into the geometries of the complex ions. Adding silver(i) to the reduced dihydro-form for cationization also induces its oxidation in solution. The oxidative dehydrogenation reaction, for which a mechanism is proposed, proceeds by first order kinetics and is markedly accelerated by day light.
CRIS-Team Scopus Importer:2023-06-23

Stabilizing Magnesium Hydride Complexes with Neutral Ligands - Wiesinger, Michael; Maitland, Brant; Elsen, Holger; Pahl, Jürgen; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2019)
The reaction of Mg[N(SiMe3)(2)](2) with PhSiH3 in benzene at room temperature gave a white precipitate of approximate constitution MgH1.5N ''(0.5). This undefined hydride rich Mg salt can be dissolved by addition of well-known neutral donors, such as PMDTA, DABCO or the N-heterocyclic carbene I(Me)iPr (N,N '-diisopropyl-2,3-dimethylimidazol-2-ylidine). This allowed for crystallization and structural characterization of five new magnesium hydride complexes: Mg-2(mu-H)(2)N ''(2)center dot(PMDTA) (1), Mg-4(mu-H)(6)N ''(2)center dot(PMDTA)(2) (2), Mg-5(mu-H)(7)N ''(3)center dot(PMDTA)(2) (3), Mg-2(mu-H)(2)N ''(2)center dot(DABCO)(2) (4) and Mg-2(mu-H)(2)N ''(2)center dot(I(Me)iPr)(2) (5). The PMDTA complexes 1-3 were only isolated as mixtures that could not be separated but complexes 4 and 5 have been fully characterized. The structures of the Mg hydride complexes 1, 4 and 5 are reproduced well by DFT calculations (B3PW91/6-311++G**). Bonding between Mg and hydride is largely ionic (circa 80 %) and there is very little charge transfer from the neutral donor to Mg2+. The calculated solvation enthalpies (Delta H-solv) per ligand are -12.4 kcal/mol (PMDTA), -15.9 kcal/mol (DABCO) and -20.8 kcal/mol (I(Me)iPr). In complexes 4 and 5 Bond-Critical-Points are found between the two negatively charged hydride ligands. The very high electron densities of 0.15-0.16 e/angstrom(3) in these unusual BCP's are related to the short H-center dot center dot center dot H- distances of circa 2.55 angstrom.
CRIS-Team WoS Importer:2019-10-25

Strongly reducing magnesium(0) complexes - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Langer, Jens; Elsen, Holger; Harder, Sjoerd (Nature, 2021)
A complex of a metal in its zero oxidation state can be considered a stabilized, but highly reactive, form of a single metal atom. Such complexes are common for the more noble transition metals. Although rare examples are known for electronegative late-main-group p-block metals or semimetals1-6, it is a challenge to isolate early-main-group s-block metals in their zero oxidation state7-11. This is directly related to their very low electronegativity and strong tendency to oxidize. Here we present examples of zero-oxidation-state magnesium (that is, magnesium(0)) complexes that are stabilized by superbulky, monoanionic, β-diketiminate ligands. Whereas the reactivity of an organomagnesium compound is typically defined by the nucleophilicity of its organic groups and the electrophilicity of Mg2+ cations, the Mg0 complexes reported here feature electron-rich Mg centres that are nucleophilic and strongly reducing. The latter property is exemplified by the ability to reduce Na+ to Na0. We also present a complex with a linear Mg3 core that formally could be described as a MgI-Mg0-MgI unit. Such multinuclear mixed-valence Mgn clusters are discussed as fleeting intermediates during the early stages of Grignard reagent formation. Their remarkably strong reducing power implies a rich reactivity and application as specialized reducing agents.
CRIS-Team Scopus Importer:2021-05-14

Unsupported Mg-Alkene Bonding - Thum, Katharina; Friedrich, Alexander; Pahl, Jürgen; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2020)
The first intermolecular early main group metal-alkene complexes were isolated. This was enabled by using highly Lewis acidic Mg centers in the Lewis base-free cations ((BDI)-B-Me)Mg+ and ((BDI)-B-tBu)Mg+ with B(C6F5)(4)(-) counterions ((BDI)-B-Me=CH[C(CH3)N(DIPP)](2), (BDI)-B-tBu=CH[C(tBu)N(DIPP)](2), DIPP=2,6-diisopropylphenyl). Coordination complexes with various mono- and bis-alkene ligands, typically used in transition metal chemistry, were structurally characterized for 1,3-divinyltetramethyldisiloxane, 1,5-cyclooctadiene, cyclooctene, 1,3,5-cycloheptatriene, 2,3-dimethylbuta-1,3-diene, and 2-ethyl-1-butene. In all cases, asymmetric Mg-alkene bonding with a short and a long Mg-C bond is observed. This asymmetry is most extreme for Mg-(H2C=CEt2) bonding. In bromobenzene solution, the Mg-alkene complexes are either dissociated or in a dissociation equilibrium. A DFT study and AIM analysis showed that the C=C bonds hardly change on coordination and there is very little alkene -> Mg electron transfer. The Mg-alkene bonds are mainly electrostatic and should be described as Mg2+ ion-induced dipole interactions.
CRIS-Team WoS Importer:2021-01-15